Fluorine-doped high-entropy metal oxide nanosheet, preparation method and application thereof

CN122916221APending Publication Date: 2026-10-16NAT UNIV OF DEFENSE TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611120084.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]本发明的目的之一,是提供一种氟掺杂高熵金属氧化物纳米片的制备方法,通过原位发泡构筑二维形貌-气相氟化改性的一体化制备路线,既解决了通用高熵氧化物制备依赖外模板或复杂液相工艺、二维形貌调控难度大、阴离子掺杂工艺与形貌保持相冲突的行业共性难题;又解决了面向锂金属负极改性的场景时,高熵氧化物需要同时具备平整二维形貌与可控氟掺杂、现有拼接式工艺会导致纳米片坍塌、掺杂不均的问题

Benefits of technology

[0024] The second objective of this invention is to provide a fluorine-doped high-entropy metal oxide nanosheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916221A_ABST
    Figure CN122916221A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion battery manufacturing, and discloses fluorine-doped high-entropy metal oxide nanosheets, a preparation method thereof and application. The preparation method of the fluorine-doped high-entropy metal oxide nanosheets comprises the following steps: S1, mixing a carbon source, an oxidizing nitrogen source and a nitrate oxidant to obtain a mixture; S2, performing heat treatment on the mixture to make the carbon source and the oxidizing nitrogen source generate a foaming reaction, and obtaining a layered carbon-containing intermediate product; S3, placing the layered carbon-containing intermediate product in an oxidizing atmosphere to remove carbon by calcination, and obtaining high-entropy metal oxide nanosheets; and S4, placing the high-entropy metal oxide nanosheets in a protective atmosphere, and making the high-entropy metal oxide nanosheets generate a gas-solid reaction with fluorine-containing gas generated by pyrolysis of a fluorinating agent to obtain fluorine-doped high-entropy metal oxide nanosheets. The method does not need an external template or complex equipment, and overcomes the difficulty that the existing high-entropy oxide preparation process is complicated and the morphology is difficult to control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of anode material technology, and in particular, to a fluorine-doped high-entropy metal oxide nanosheet, its preparation method, and its application. Background Technology

[0002] Lithium metal anodes are widely recognized as the most promising anode material for next-generation high-energy-density rechargeable batteries due to their extremely high theoretical specific capacity (3860 mAh / g) and the lowest electrochemical potential (-3.04 V). Research on lithium metal anodes has spanned decades, with the industry exploring various technological pathways to promote their practical applications. These strategies primarily include electrolyte additive regulation, construction of artificial SEI films (solid electrolyte interface films), three-dimensional current collector design, and the creation of functional protective coatings on the lithium metal surface.

[0003] Among them, surface coating technology is considered one of the most engineering-feasible solutions because it can directly isolate the physical contact between lithium metal and electrolyte and is relatively simple to operate. Currently, a variety of coating systems, including inorganic oxides, nitrides, polymers and composite coatings, have been developed.

[0004] However, existing surface coating technologies still face fundamental performance bottlenecks. While the physical barrier effect of the coating can delay the corrosion of lithium metal by the electrolyte to some extent, it cannot actively regulate the deposition behavior of lithium ions on the negative electrode surface. After passing through the coating, lithium ions still tend to preferentially nucleate and grow into dendritic lithium at local defects or protrusions. The continuous growth of dendrites eventually penetrates the weak areas of the coating, causing micro-short circuits or even thermal runaway inside the battery. The above problems mainly stem from the fact that existing coating materials essentially only provide passive physical isolation functions, lacking strong and uniformly distributed chemical interaction sites with lithium ions. They cannot intervene in the nucleation and growth process of lithium ions at the source, thus making it difficult to simultaneously solve the two core contradictions of interface protection and deposition regulation. In existing technologies, to address these dual needs, researchers usually use multilayer functional coatings or add multiple functional additives to the electrolyte to achieve a superposition of protection and regulation. That is, setting an outer protective layer to block the electrolyte and an inner lithiophilic layer to guide deposition, or modifying the interface in situ in the electrolyte with additives.

[0005] However, this stacking strategy faces significant technical obstacles: First, the multilayer coating system suffers from poor interfacial compatibility, complex preparation processes, and the layers are prone to peeling or deactivation during long-term cycling; second, additives are limited by their consumption in the electrolyte and diffusion mass transfer constraints, making it difficult to form a long-term stable and effective interfacial layer on the electrode surface. These obstacles make it difficult for existing solutions to simultaneously achieve long-term cycling stability, process simplicity, and electrode structural reliability. Summary of the Invention

[0006] One of the objectives of this invention is to provide a method for preparing fluorine-doped high-entropy metal oxide nanosheets. This method utilizes an integrated preparation route that combines in-situ foaming to construct a two-dimensional morphology with gas-phase fluorination modification. This approach solves the common industry problems of high-entropy oxide preparation, such as reliance on external templates or complex liquid-phase processes, difficulty in controlling the two-dimensional morphology, and conflicts between anion doping processes and morphology maintenance. Furthermore, it addresses the issues in lithium metal anode modification scenarios, where high-entropy oxides need to simultaneously possess a flat two-dimensional morphology and controllable fluorine doping, and where existing splicing processes lead to nanosheet collapse and uneven doping.

[0007] To achieve the above-mentioned objectives, the specific technical solution is as follows: A method for preparing fluorine-doped high-entropy metal oxide nanosheets includes the following steps: S1 mixes a carbon source, an oxidizing nitrogen source, and a nitrate oxidant to obtain a mixture, wherein the nitrate oxidant is a nitrate oxidant containing at least five metal elements; S2 heat-treats the mixture to cause a foaming reaction between the carbon source and the oxidizing nitrogen source, thereby obtaining a layered carbon-containing intermediate product. The heat treatment temperature is 400~700℃. S3 The layered carbon-containing intermediate product is calcined in an oxidizing atmosphere to remove carbon, thereby obtaining high-entropy metal oxide nanosheets. S4 The high-entropy metal oxide nanosheets are placed in a protective atmosphere and react with the fluorine-containing gas generated by the pyrolysis of the fluorinating agent to obtain fluorine-doped high-entropy metal oxide nanosheets; in the gas-solid reaction, the fluorinating agent is arranged upstream of the gas flow of the high-entropy metal oxide nanosheets, and the hydrogen fluoride generated by the thermal decomposition of the fluorinating agent flows through the nanosheet surface with the gas flow to complete the bulk phase uniform doping. The carbon source is a carbon-containing reducing organic compound, and the oxidizing nitrogen source is a nitrate oxidant that decomposes upon heating to produce gas.

[0008] According to embodiments of the present invention, one of the technical solutions has at least one of the following advantages or beneficial effects: In existing technologies, the two-dimensional morphology of high-entropy oxides is often uncontrollable, and the fluorine doping process is complex and easily damages the material structure. At the same time, the preparation of the two-dimensional morphology of high-entropy oxides and fluorine doping are often two independent processes in existing technologies (such as template preparation and wet doping). In the process of solving this problem, if the two independent processes of morphology preparation and doping modification are forcibly combined, it will often cause damage to the nanosheet structure and uneven doping.

[0009] This invention generates gas in situ through the foaming reaction of carbon source and oxidizing nitrogen source in S2, causing the melt to expand spontaneously and form a layered precursor. This eliminates the need for external templates or complex equipment, overcoming the difficulties of cumbersome and difficult-to-control morphology preparation processes in existing high-entropy oxides. At the same time, the layered porous structure formed by foaming not only shapes the two-dimensional morphology but also provides a larger specific surface area and abundant gas phase diffusion channels, making the fluorination reaction in S4 more uniform and complete. The doping depth and uniformity are significantly better than those of gas phase doping of ordinary particulate materials. S4 employs gas-solid fluorination, where fluorides generated by the decomposition of fluorinating agents are uniformly incorporated into the high-entropy metal oxide nanosheet lattice, solving the problems of uncontrollable fluorine doping and complex processes. At the same time, the mild reaction conditions of gas-phase fluorination do not destroy the layered structure formed by foaming, ensuring the integrity of the two-dimensional morphology.

[0010] Furthermore, the fluorine-doped high-entropy metal oxide nanosheets prepared by the method of the present invention have a two-dimensional sheet-like morphology and a controllable fluorine-doped lattice structure. When used as a lithium anode coating, they can form a double-layer SEI in situ at the interface. The outer layer is rich in inorganic phase, which provides high mechanical strength protection, while the inner layer is a high-entropy lithium-based alloy, which provides uniform lithium-loving adsorption sites. This can minimize dendrites and side reactions in the lithium metal anode.

[0011] According to one embodiment of the present invention, the carbon source is glucose, and the oxidizing nitrogen source is ammonium nitrate. Glucose, as a carbon-containing reducing agent and structural precursor, first melts to form a liquid phase during heating, then gradually undergoes a Maillard reaction and carbonizes. Ammonium nitrate, as an oxidizing agent, decomposes upon heating and undergoes a redox reaction with the molten glucose, continuously releasing gas and driving the expansion and foaming of the molten system. Therefore, the molten liquid phase provided by glucose is a prerequisite for foaming; without a plastic melt, the gas cannot drive the system to expand and form a layered structure. The gas production of ammonium nitrate is the driving force for morphological expansion; without continuous gas release, the molten system cannot spontaneously form a two-dimensional porous structure.

[0012] According to one embodiment of the present invention, the nitrate oxidant is selected from at least five of zinc nitrate, manganese nitrate, gallium nitrate, indium nitrate, magnesium nitrate, and lithium nitrate, and each metal element is fed in an equimolar ratio.

[0013] These nitrate oxidants decompose into their corresponding oxides during heat treatment, and the five elements coexist in a near equimolar ratio in a single-phase lattice, forming a high-entropy configuration. The elements in these nitrate oxidants have similar ionic radii and moderate electronegativity, enabling them to form stable rock salt or spinel structures, and all possess moderate lithiophilicity.

[0014] Furthermore, when all metal elements are fed in an equimolar ratio, the resulting high-entropy lattice with an equimolar ratio has abundant oxygen vacancy formation energy, which is conducive to the uniform entry of fluoride ions into the lattice in the form of replacing oxygen sites, rather than just accumulating on the surface.

[0015] According to one embodiment of the present invention, the nitrate oxidant is zinc nitrate, manganese nitrate, gallium nitrate, magnesium nitrate, and lithium nitrate; or it is zinc nitrate, manganese nitrate, gallium nitrate, magnesium nitrate, and indium nitrate.

[0016] According to one embodiment of the present invention, the heat treatment in S2 includes the following steps: after heating the muffle furnace to a specified temperature, the mixture in S1 is placed in the muffle furnace and kept at that temperature.

[0017] According to one embodiment of the present invention, the heating rate of the heat treatment in S2 is 10-12 °C / min.

[0018] According to one embodiment of the present invention, the holding time of the heat treatment in S2 is 3 min to 15 min. The appropriate temperature and holding time allow the mixture to foam and form a loose, porous structure, thereby matching the calcination temperature in S3 and improving the uniformity and completeness of calcination.

[0019] According to one embodiment of the present invention, the heat treatment holding time in S2 is 3 min to 10 min.

[0020] According to one embodiment of the present invention, the calcination temperature for decarbonization in step S3 is 400~700℃. The loose, porous structure formed by foaming increases the permeability of the calcination atmosphere, resulting in more complete and uniform carbon oxidation and avoiding localized residual carbon. Furthermore, the crystallization shrinkage of the oxides during calcination gives the nanosheets appropriate mechanical strength, facilitating subsequent fluorination and coating operations.

[0021] According to one embodiment of the present invention, the fluorinating agent in S4 is ammonium fluoride, and the protective atmosphere is argon. In this embodiment, the metal elements are uniformly distributed in the high-entropy oxide. Although the HF produced by the decomposition of ammonium fluoride has varying reactivity with different metal-oxygen bonds, driven by high-entropy disorder, fluoride ions tend to substitute evenly rather than preferentially substituting the oxygen sites of a particular metal, thus achieving uniform bulk doping. This differs from the tendency for surface segregation to occur during the fluorination of single metal oxides; it is an additional synergistic advantage brought about by the high-entropy configuration of uniformly distributed metal elements.

[0022] According to one embodiment of the present invention, the heating temperature for the pyrolysis of the fluorinating agent in S4 is 150~350°C, and the treatment time is 0.5~5h.

[0023] The optimal temperature range for the effective decomposition of fluorinating agents to produce HF is 150–350 °C. Below 150 °C, the decomposition rate is too slow, while above 350 °C, irreversible phase transitions or excessive lattice distortion may occur in high-entropy metal oxides. A processing time of 0.5–5 h can cover a fluorine doping range of 5–20 at.%, with shorter times resulting in lower doping levels and longer times resulting in higher doping levels, thus achieving on-demand control.

[0024] The second objective of this invention is to provide a fluorine-doped high-entropy metal oxide nanosheet.

[0025] To achieve the above-mentioned objectives, the specific technical solution is as follows: A fluorine-doped high-entropy metal oxide nanosheet is prepared by the method for preparing fluorine-doped high-entropy metal oxide nanosheets; The fluorine-doped high-entropy metal oxide nanosheets have a two-dimensional sheet-like morphology, with fluorine uniformly doped in the high-entropy metal oxide lattice. The fluorine doping content is 5 at.% to 20 at.%, the nanosheet thickness is 10 to 100 nm, and the lateral dimension is 1 to 10 μm.

[0026] Among them, the lithium anode coating needs to be thin and dense. If the nanosheets are too thick, the overall coating will be too thick, which will increase the polarization of lithium ion transport. If the lateral size is too small, there will be many pores after the layers are stacked, and the electrolyte will easily penetrate and cause side reactions.

[0027] With a thickness of 10~100 nm and a lateral dimension of 1~10 μm, a two-dimensional structure with a suitable aspect ratio is formed. After coating, a continuous and flat coating can be formed, which ensures both rapid ion transport and interface barrier effect.

[0028] The fluorine doping content ranges from 5 at.% to 20 at.%, indicating that under a high-entropy configuration with uniform metal element distribution, the distribution of fluorine ions is entropy-averaged, preventing them from clustering around any particular metal even at higher doping levels, thus avoiding the precipitation of localized fluorine-rich phases. This makes the adjustable range of fluorine doping content much wider than that of single-metal oxides, providing a broader process window for performance optimization.

[0029] A third objective of this invention is to provide applications for the aforementioned fluorine-doped high-entropy metal oxide nanosheets.

[0030] The specific technical solution is as follows: A modified lithium metal anode includes a lithium metal substrate and a functional coating loaded on the surface of the lithium metal substrate; the functional coating includes fluorine-doped high-entropy metal oxide nanosheets; the functional coating transforms in situ into a bilayer structure of an outer LiF / Li2O-rich inorganic protective layer and an inner high-entropy lithium-based alloy inducing layer during battery cycling.

[0031] In existing technologies, the problems of lithium dendrite growth and interfacial side reactions need to be solved by two separate solutions. For example, a physical barrier solution can be used to solve the side reactions, while an alloy-induced solution can be used to solve the dendrites. However, simply stacking the two solutions into a multilayer coating would lead to more complex processes and poorer interfacial adhesion.

[0032] The functional coating of the present invention can react and differentiate into a bilayer functional structure in situ during the cycling process, without the need to prepare a multilayer coating in advance. This simplifies the preparation process and avoids the transport resistance and delamination risk of multilayer interfaces.

[0033] Specifically, after fluorine-doped high-entropy oxide nanosheets are coated on the lithium surface, they undergo a reduction reaction with metallic lithium during the first charge-discharge process: fluorine combines with lithium to form LiF, and oxygen combines with lithium to form Li₂O, together forming a dense outer inorganic protective layer; various metal elements in the oxide alloy with lithium to form a high-entropy lithium-based alloy induction layer, located between the inorganic layer and the lithium substrate, regulating the lithium deposition behavior. Ultimately, a dual-functional interface of outer protection and inner induction is formed in situ.

[0034] According to one embodiment of the present invention, the functional coating is prepared by fluorine-doped high-entropy metal oxide nanosheets, binder and solvent into a slurry, which is then coated onto the surface of a lithium metal substrate and dried.

[0035] According to one embodiment of the present invention, the adhesive is polyvinylidene fluoride or polyvinylidene fluoride-hexafluoropropylene copolymer, and the solvent is N-methylpyrrolidone or butanone.

[0036] A lithium-ion battery comprising the modified lithium metal anode.

[0037] In addition to the objectives, features and advantages described above, the present invention has other objectives, features and advantages. Attached Figure Description

[0038] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which: Figure 1 The image shows the transmission electron microscope (TEM) and energy dispersive spectroscopy (EDS) results of the fluorine-doped high-entropy metal oxide nanosheets prepared in Example 1.

[0039] Figure 2 X-ray diffraction patterns of the fluorine-doped high-entropy metal oxide nanosheets prepared in Example 1 and the nanosheets prepared in Comparative Example 2.

[0040] Figure 3 The image shows the characterization of the FHEOs-modified lithium anode in Example 1.

[0041] Figure 4The image shows a characterization comparison between the FHEOs-modified lithium anode in Example 1 and the lithium anode in Comparative Example 1.

[0042] Figure 5 This is a comparison chart of the rate performance of the lithium-ion battery in Example 1 and the lithium-ion battery in Comparative Example 1.

[0043] Figure 6 The diagram shows the cycle test results of the lithium-ion batteries in Example 1 and Comparative Example 1. Detailed Implementation

[0044] The terms "preferred," "more preferred," etc., used in this invention refer to embodiments of the invention that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this invention.

[0045] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0046] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of the present invention.

[0047] Unless otherwise specified, the reagents, methods and equipment used in this invention are all conventional reagents, methods and equipment in this technical field.

[0048] In the examples and comparative examples, the fluorine doping content was determined by energy dispersive spectroscopy (EDS).

[0049] Example 1 A method for preparing fluorine-doped high-entropy metal oxide nanosheets comprises the following steps: S1 is prepared by weighing zinc nitrate, manganese nitrate, gallium nitrate, magnesium nitrate, and lithium nitrate according to the molar ratio of metal elements Zn:Mn:Ga:Mg:Li = 1:1:1:1:1, and mixing them with glucose (1.5 times the total mass of nitrate oxidants) and ammonium nitrate (0.8 times the total mass of nitrate oxidants). The mixture is then ground thoroughly in a mortar for 30 minutes to obtain the final mixture. S2 The muffle furnace was heated to 550°C in air at a heating rate of 10°C / min; the mixture was transferred to a corundum crucible, placed in the muffle furnace, and held at that temperature for 10 min. During this time, obvious foaming and expansion phenomena were observed, and a black, fluffy foam-like product (carbon-containing intermediate product) was obtained. S3 calcined the above black fluffy foam product at 700°C for 2 hours in air atmosphere to remove carbon components and obtain white high entropy metal oxide (HEO) nanosheet powder, denoted as ZnMnGaMgLi-O. S4. Take 0.03 g of the above-mentioned white high-entropy metal oxide and place it in the center of a tube furnace. Place 0.5 g of NH4F powder in the upstream region of the tube furnace inlet and introduce argon gas (flow rate 50 sccm). Heat the furnace to 350℃ at 5℃ / min and hold for 2 hours. After naturally cooling to room temperature, take out the product, which is fluorine-doped high-entropy metal oxide nanosheets (FHEOs), denoted as F-ZnMnGaMgLi-O.

[0050] The fluorine-doped high-entropy metal oxide nanosheets prepared in Example 1 were tested by transmission electron microscopy (TEM) and energy dispersive spectroscopy (EDS). The test results are as follows: Figure 1 , Figure 1 Transmission electron microscopy (TEM) images and energy dispersive spectroscopy (EDS) scans show that the fluorine-doped high-entropy metal oxide nanosheets prepared in Example 1 have a two-dimensional nanosheet morphology.

[0051] X-ray diffraction tests were performed on the fluorine-doped high-entropy metal oxide nanosheets prepared in Example 1 and the nanosheets prepared in Comparative Example 2. The test results are as follows: Figure 2 , Figure 2 The nanosheets of Example 1 and Comparative Example 2 both exhibit single-phase rock salt or spinel structural characteristics.

[0052] A method for preparing an FHEOs-modified lithium anode comprises the following steps: Fluorine-doped high-entropy metal oxide nanosheets and PVDF binder were mixed at a mass ratio of 8:2, and an appropriate amount of NMP solvent was added. The mixture was magnetically stirred for 12 hours to form a uniform slurry. The slurry was then uniformly coated onto the surface of a 200 μm thick lithium foil using a doctor blade coating method, with the coating thickness controlled at 50 μm (wet film). The coated lithium foil was then placed in a vacuum oven and dried at 60 °C for 12 hours to obtain the FHEOs-modified lithium anode (FHEOs-Li).

[0053] Figure 3 The image shows the characterization of the FHEOs-modified lithium anode (FHEOs-Li) in Example 1. Figure 3 (a) is a surface SEM image. Figure 3 (b) is the surface distribution diagram of EDS elements. Figure 3 Image (c) is a cross-sectional electron microscope scan image. Among them, Figure 3 (c) shows that the thickness of the lithium anode coating is about 2.28 μm. The interface between the coating and the lithium substrate is clear and tightly bonded, with no peeling.

[0054] A method for preparing a lithium-ion battery includes the following steps: The above-mentioned FHEOs-Li anode, Celgard 2400 separator, and lithium iron phosphate (LiFePO4) cathode were assembled into a CR2032 coin cell. The electrolyte was 1 M LiPF6 dissolved in EC / DEC at a volume ratio of 1:1, with 2 wt% FEC added.

[0055] Figure 4 The image shows a comparison of the lithium-ion battery characterization of Example 1 and Comparative Example 1 after cycle testing. The cycle count was 500 cycles, conducted under constant current charge-discharge cycle conditions of 1 / 3C charging and 1C discharging. Figure 4 (a) is a SEM image of the lithium anode of Comparative Example 1. Figure 4 (b) is a cross-sectional scanning electron microscope image of the lithium anode in Comparative Example 1. Figure 4 (c) is a surface SEM image of the FHEOs-modified lithium anode (FHEOs-Li) of Example 1. Figure 4 (d) is a cross-sectional scanning electron microscope image of the FHEOs modified lithium anode of Example 1. Figure 4 As can be seen, after cycling, electron microscopy revealed a dense and smooth layered lithium deposition morphology on the surface of the lithium anode in Example 1, without dendrites. Furthermore, the total thickness of the deposition layer and interface layer on the anode surface of Comparative Example 1 after cycling was 24.76 μm; the thickness of FHEOs-Li in Example 1 was 6.15 μm, which is... Figure 3 Compared to (c), the thickness increased only to 6.15 μm after cycling (approximately 2.7 times the initial thickness of 2.28 μm), which is far superior to Comparative Example 1 (approximately 10.8 times the initial thickness), demonstrating that the coating of the present invention can effectively suppress dendrite growth and reduce side reactions.

[0056] Figure 5 This is a comparison chart of the rate performance of the lithium-ion battery in Example 1 and the lithium-ion battery in Comparative Example 1. Figure 5In the test, the voltage window was 3.0-4.4V, the test temperature was 25℃, and the test was first cycled 10 times at 0.5C rate, then 10 times at 1C rate, 10 times at 2C rate, 10 times at 5C rate, and finally 10 times at 0.5C rate. The test found that after the battery of Example 1 was tested at 0.5C-5C rate, the discharge specific capacity of the battery at 0.5C rate could be restored to the value of the first 0.5C test. This shows that the battery of Example 1 has less irreversible damage at high rates and good rate performance.

[0057] Example 2 The difference between Example 2 and Example 1 is that the fluorination treatment time (heating time) in S4 of Example 2 is 0.5h, while other conditions remain unchanged, resulting in an FHEOs sample with a fluorine doping content of 5 at.%.

[0058] Example 3 The difference between Example 3 and Example 1 is that the fluorination treatment time (heating time) in S4 of Example 3 is set to 1 hour, while other conditions remain unchanged, resulting in an FHEOs sample with a fluorine doping content of 6 at.%.

[0059] Example 4 The difference between Example 4 and Example 1 is that the fluorination treatment time (heating time) in S4 of Example 4 is set to 3h, while other conditions remain unchanged, resulting in an FHEOs sample with a fluorine doping content of 16 at.%.

[0060] Example 5 The difference between Example 5 and Example 1 is that the fluorination treatment time (heating time) in S4 of Example 5 is set to 5h, while other conditions remain unchanged, resulting in an FHEOs sample with a fluorine doping content of 20 at.%.

[0061] Example 6 The difference between Example 6 and Example 1 is that PVDF-HFP is used instead of PVDF in Example 1 as the adhesive in Example 6, while other conditions are the same as in Example 1.

[0062] Among them, PVDF-HFP has excellent flexibility and affinity for electrolyte, which helps maintain the structural integrity of the coating during long-term cycling. The battery of Example 6 was subjected to constant current charge-discharge cycle test under the condition of 1 / 3C charge and 1C discharge rate. The test showed that its capacity retention rate was about 90% after 400 cycles, which was comparable to that of Example 1.

[0063] Example 7 The difference between Example 7 and Example 1 is that the molar ratio of the metal elements in S1 is different. In S1 of Example 7, zinc nitrate, manganese nitrate, gallium nitrate, magnesium nitrate and indium nitrate are weighed according to the molar ratio of metal elements Zn:Mn:Ga:Mg:In= 1:1:1:1:1, and other conditions are the same as in Example 1 to prepare FHEOs modified lithium anode.

[0064] In, with its excellent lithium affinity, forms a high-entropy alloy layer, which also helps maintain the structural integrity of the coating during long-term cycling. The battery from Example 7 was subjected to constant current charge-discharge cycle testing under 1 / 3C charging and 1C discharging conditions. The test showed that after 400 cycles, the capacity retention was approximately 90%, comparable to Example 1.

[0065] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses pure lithium metal foil as the negative electrode without any surface modification.

[0066] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses the same method to prepare nanosheets as Example 1, but does not perform fluorine doping. The nanosheets prepared in Comparative Example 2 are named HEOs nanosheets. They are coated on the surface of lithium metal as a control sample.

[0067] The battery of Comparative Example 2 was subjected to constant current charge-discharge cycle test under the conditions of 1 / 3C charging and 1C discharging. During the cycle, the uniformity of lithium deposition morphology of the battery of Comparative Example 2 was improved compared with pure lithium (Comparative Example 1). However, due to the lack of high mechanical strength protection of the inorganic outer layer, local dendrite growth appeared after long cycle. Dendrites appeared within 100 cycles, and the coulombic efficiency fluctuated significantly. The coulombic efficiency dropped to below 95% after 200 cycles.

[0068] Performance testing: Figure 6 This is a comparison chart of the cycle performance of lithium-ion batteries in Example 1 and Comparative Example 1. Constant current charge-discharge cycle tests were conducted under 1 / 3C charging and 1C discharging rates. The results show that the battery in Example 1 retained more than 92% of its capacity after 500 cycles, with an average coulombic efficiency of 99.6%.

[0069] The fluorine doping content of the fluorine-doped high-entropy metal oxide nanosheets in Examples 1-7 was tested using transmission electron microscopy-energy dispersive spectroscopy (EDS), and the test results are shown in Table 1.

[0070] Table 1. Fluorine doping content of fluorine-doped high-entropy metal oxide nanosheets in Examples 1-7

[0071] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0072] The above embodiments merely illustrate several implementation methods of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of the present invention should be determined by the appended claims.

[0073] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing fluorine-doped high-entropy metal oxide nanosheets, characterized in that, Includes the following steps: S1 mixes a carbon source, an oxidizing nitrogen source, and a nitrate oxidant to obtain a mixture, wherein the nitrate oxidant is a nitrate oxidant containing at least five metal elements; S2 heat-treats the mixture to cause a foaming reaction between the carbon source and the oxidizing nitrogen source, thereby obtaining a layered carbon-containing intermediate product. The heat treatment temperature is 400~700℃. S3 The layered carbon-containing intermediate product is calcined in an oxidizing atmosphere to remove carbon, thereby obtaining high-entropy metal oxide nanosheets. S4 The high-entropy metal oxide nanosheets are placed in a protective atmosphere and react with the fluorine-containing gas generated by the pyrolysis of the fluorinating agent to obtain fluorine-doped high-entropy metal oxide nanosheets; in the gas-solid reaction, the fluorinating agent is arranged upstream of the gas flow of the high-entropy metal oxide nanosheets, and the hydrogen fluoride generated by the thermal decomposition of the fluorinating agent flows through the nanosheet surface with the gas flow to complete the bulk phase uniform doping. The carbon source is a carbon-containing reducing organic compound, and the oxidizing nitrogen source is a nitrate oxidant that decomposes upon heating to produce gas.

2. The method for preparing fluorine-doped high-entropy metal oxide nanosheets according to claim 1, characterized in that, The carbon source is glucose, and the oxidizing nitrogen source is ammonium nitrate.

3. The method for preparing fluorine-doped high-entropy metal oxide nanosheets according to claim 1, characterized in that, The nitrate oxidant is selected from at least five of the following: zinc nitrate, manganese nitrate, gallium nitrate, indium nitrate, magnesium nitrate, and lithium nitrate, and each metal element is fed in an equimolar ratio.

4. The method for preparing fluorine-doped high-entropy metal oxide nanosheets according to claim 3, characterized in that, The nitrate oxidant is zinc nitrate, manganese nitrate, gallium nitrate, magnesium nitrate, and lithium nitrate; or it is zinc nitrate, manganese nitrate, gallium nitrate, magnesium nitrate, and indium nitrate.

5. The method for preparing fluorine-doped high-entropy metal oxide nanosheets according to claim 1, characterized in that, The heat treatment holding time described in S2 is 3 min to 15 min.

6. The method for preparing fluorine-doped high-entropy metal oxide nanosheets according to claim 1, characterized in that, The calcination temperature for carbon removal described in S3 is 400~700℃.

7. The method for preparing fluorine-doped high-entropy metal oxide nanosheets according to claim 1, characterized in that, The fluorinating agent mentioned in S4 is ammonium fluoride, and the protective atmosphere is argon.

8. The method for preparing fluorine-doped high-entropy metal oxide nanosheets according to claim 1, characterized in that, The heating temperature for the pyrolysis of the fluorinating agent described in S4 is 150~350℃, and the treatment time is 0.5~5h.

9. A fluorine-doped high-entropy metal oxide nanosheet, characterized in that, Prepared by the method for preparing fluorine-doped high-entropy metal oxide nanosheets according to any one of claims 1-8; The fluorine-doped high-entropy metal oxide nanosheets have a two-dimensional sheet-like morphology, with fluorine uniformly doped in the high-entropy metal oxide lattice. The fluorine doping content is 5 at.% to 20 at.%, the nanosheet thickness is 10 to 100 nm, and the lateral dimension is 1 to 10 μm.

10. A modified lithium metal anode, characterized in that, It includes a lithium metal substrate and a functional coating loaded on the surface of the lithium metal substrate; the functional coating includes fluorine-doped high-entropy metal oxide nanosheets as described in claim 9; the functional coating will transform in situ into a bilayer structure of an outer LiF / Li2O rich inorganic protective layer and an inner high-entropy lithium-based alloy inducing layer during battery cycling.